Content Pillar sebagai Strategi Pengelolaan Konten Instagram @finpaypromo - Agustin, Fira; Diniati, Anisa (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The increasingly developing digital era requires every company to be able to actively utilize social media in disseminating information about its products. PT Finnet Indonesia also uses social media to build awareness of its Finpay brand and disseminate information related to fintech products and industries. The purpose of this study is to find out the strategy used by the Finpay social media team in managing Instagram @finpaypromo content. This research was analyzed using The Circular Model of SoMe by Lutrell (2022) and the supporting concept, namely Public Relations Strategy by Cutlip Center (2013). This study uses a qualitative approach with a descriptive type. The results of the study show that Instagram content management strategies @finpaypromo carried out by checking content performance, trend research, competitor analysis to find out potential content and in accordance with audience preferences. Finpay also has a content pillar that is useful as a guide in producing content, content plans, and posting timelines that are useful in the production process and content posting plans. In addition, Finpay is also developing an engagement strategy with the audience through content that focuses more on copy and call to action.